Effect of COVID-19 Pandemic on Community-Based Homestay Tourism in the Buffer Zone of Chitwan National Park (OCEM Journal of Management, Technology & Social Sciences, 2025)
Tourism is a key driver of economic growth and a vital component of sustainable development, linking sectors such as transportation, accommodation, and cultural experiences. It enhances local livelihoods, particularly through community-based ecotourism initiatives like homestays. This study assessed the socioeconomic effects of the COVID-19 pandemic on homestay operators and their coping strategies in Amaltari Tharu village homestay, located in the bufferzone of Chitwan National Park, Nepal. The research aimed to evaluate the pandemic’s impact on livelihoods and identify adaptive strategies for recovery. Household surveys (n=31) and focus group discussions were employed, with data analyzed using t-tests, Chi-square tests, and descriptive statistics. SWOT analysis was conducted among the stakeholders to find the strategic position of homestay tourism in the post pandemic situation. The pandemic significantly impacted the livelihoods of people dependent on ecotourism. The study revealed that the proportion of respondents reporting little or no earnings increased significantly from 16.1% to 77.4% during the pandemic, reflecting the severe impact of the pandemic on livelihoods. There was substantial decline in the average gross monthly income of homestay operators, confirming significant reductions in income levels and sufficiency after the lockdown.  Overall, the study highlights the adverse effects of the pandemic on community-based homestay tourism in buffer-zone area, emphasizing the need for adaptive alternative livelihood strategies and policy support like provision of soft loan, operation capital, motivational training on safety measures and the promotional activities by the respective authority to operate and revive the homestay tourism in its rhythm in the new normal situation.